Wednesday

October 1, 2014

October 1, 2014

Posted by **Marcel** on Tuesday, September 7, 2010 at 4:42am.

- advanced math -
**jai**, Tuesday, September 7, 2010 at 4:57amsince there is e^4t multiplied to cos(2t), there is s-shifting:

from e^4t, we know that a = 4,, we also know that L{cos 2t} = s/(s^2 + 4) , therefore:

L{e^4t(cos 2t)} = (s-a)/((s-a)^2 + 4) = (s-4)/((s-4)^2 + 4)

so there,, =)

- advanced math -
**Marcel**, Tuesday, September 7, 2010 at 5:27amthanks a bunch.

**Answer this Question**

**Related Questions**

calc 2 - (last one) ... Let f(t) be a function defined for all values of t. The...

Calc2 - Let f(t) be a function defined for all values of t. The Laplace ...

college math - the Laplace transform of e^4t(cos 2t)?? please i need help. ...

Calculus-HELP!!! - Find the Laplace transform of: f(t) = cos^(2)(2t)

Calculus-HELP!!! - Find the Laplace transform of: f(t) = cos^(2)(2t)

calculus - Solve the DE by using the Laplace transform: x''+x=cos(3t), x(0)=x'(...

Math - What is the laplace transform of (t^2)sin(t)?

Math - Using the table Laplace transform, determine the function f (t) of the ...

ODE - what is the laplace transform of 5/2.e^t-3/2.e^-t

Calc 3 - What is the laplace transform of: f(t) = 0, 0<t<2 t, 2<t ...